Economic Journal in Russia: Quality Assessment Issues - Ol’ga Valentinovna Tret’yakova (Economic and Social Changes: Facts, Trends, Forecast, 2016)
The paper attempts to assess economic journals included in the List of peer-reviewed scientific journals and editions that are authorized to publish the principal research findings of doctoral (candidate’s) dissertations (the VAK List, it was established by the Decision of the Ministry of Education and Science of the Russian Federation and entered into force on December 01, 2016). The general assessment of the journals that include more than 380 titles is carried out by analyzing their bibliometric indicators in the system of the Russian Science Citation Index, in particular, by examining the values of their impact factors. The analysis conducted at the Institute of Socio-economic Development of Territories of RAS shows that a relatively small number of economic journals publish a significant proportion of articles that obtain a large share of citations. The author reveals that the new VAK List includes over 50% of journals specializing in economic sciences, which have a lower level of citation or which are virtually not cited at all. This indirectly indicates that such journals are “left behind” the “main stream of science”, that their significance is local, availability low, attractiveness for the audience and scientific authority insufficient. The analysis proves that when forming the list of peer-reviewed scientific publications recommended for publication of dissertation research findings, along with other criteria, it is advisable to use tools that help assess the level of the journal. It is very important that the evaluation had quantitative expression and served as a specific measure for ranking the journals. One of these tools may be a criterion value for the two-year impact factor, which helps identify journals with a sufficient citation level. The paper presents the results of analysis of the RSCI list, which was proposed by the Council for Science under the Ministry of Education and Science of the Russian Federation as an alternative to the new VAK List. The author draws a conclusion about the need to review the first results of the project and to continue working with them, because the issues identified still do not allow the RSCI list to be used as a full replacement for the VAK List. The paper propose options to expand the RSCI list. The author substantiates the necessity to expand the geography of journals included in the RSCI